Sarcopenia and Its Implications for Metabolic Health - Gary R. Hunter; Harshvardhan Singh; Stephen J. Carter; David R. Bryan; Gordon Fisher (Journal of Obesity)
Sarcopenia not only affects the ability to lead an active lifestyle but also contributes to increased obesity, reduced quality of life, osteoporosis, and metabolic health, in part due to reduced locomotion economy and ease. On the other hand, increased obesity, decreased quality of life, and reduced metabolic health also contribute to sarcopenia. The purpose of this mini-review is to discuss the implications sarcopenia has for the development of obesity and comorbidities that occur with aging.